The effect of metformin on the metabolic parameters in polycystic ovarian syndrome. - Dahlia Abd Malik; Mohd Hashim Omar; Nur Azurah Abdul Ghani; Ahmad Zailani Hatta; Norfilza Mokhtar; Mohamad Nasir Shafiee (Department of Surgery, UKM Medical Centre, 2014)
A total of 40 women with PCOS were recruited in this study. Baseline characteristics (menstrual history, hirsutism scoring (Ferriman Gallwey score), weight, body mass index (BMI), serum luteinizing hormone and follicule-stimulating hormone (LH:FSH) ratio, fasting glucose and fasting lipid profiles were assessed at pre and 3-months post metformin therapy.